2016
DOI: 10.1371/journal.pone.0146290
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Changes during Prolonged Stay at High Altitude and Its Correlation with C-Reactive Protein

Abstract: Hypersensitive C-reaction protein (hsCRP) may be a risk factor for cognitive impairment resulting from Alzheimer’s disease (AD), stroke, and vascular dementia. This study explored the correlation of peripheral blood hsCRP level with cognitive decline due to high altitude exposure. The study was conducted on 100 male military participants who had never been to high altitude. Cerebral oxygen saturation monitoring, event related potentials (P300, N200) detection, and neurocognitive assessment was performed and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…Until now, most studies examined this matter in real altitude with great environmental and subjects-related, constitutional influences [12, 13]. The greater parameter of reaction time was not affected as much by low FiO 2 levels during the night.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, most studies examined this matter in real altitude with great environmental and subjects-related, constitutional influences [12, 13]. The greater parameter of reaction time was not affected as much by low FiO 2 levels during the night.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment was observed in the early hours of exposure (day 0), but after 2 days no impairment in response speed was detected (days 2 and 4), although the error rate remained high . Hu et al reported that digit symbol substitution test performance was impaired during the first 3 days at high altitude (4400 m). However, cognitive performance was restored after one and 3 months .…”
Section: Combined Effects Of Acute Exercise and Hypoxiamentioning
confidence: 99%
“…Hu et al reported that digit symbol substitution test performance was impaired during the first 3 days at high altitude (4400 m). However, cognitive performance was restored after one and 3 months . Pagani et al suggested that acclimatization leads to improved cognitive performance at altitude of 5350 m. Pun et al indicated that impaired cognitive performance was restored after acclimatization.…”
Section: Combined Effects Of Acute Exercise and Hypoxiamentioning
confidence: 99%
“…This examination measures response, attention, and processing speeds (Hu et al., 2016; Wang et al., 2013). The test consists of nine digit‐symbol pairs followed by a list of digits.…”
Section: Subjectsmentioning
confidence: 99%
“…A wide range of past studies have demonstrated that hypoxia at high altitude induces neurophysiological conditions such as dizziness, insomnia, headaches, nausea, vomiting, and fatigue, and even possibly high altitude pulmonary edema, and cerebral edema that is potentially fatal (Basnyat & Murdoch, 2003). Furthermore, it could also trigger neurocognitive dysfunction including learning, memory, language, vision, and mood (Hu, Xiong, Dai, Zhao, & Feng, 2016; Wilson, Newman, & Imray, 2009). In addition, cognitive deficits may last for some time following people's coming back to sea level from plateau (Bonnon, Noel‐Jorand, & Therme, 2000).…”
Section: Introductionmentioning
confidence: 99%